WARISAN PENGETAHUAN LELUHUR: SISTEM PEMBELAJARAN MASYARAKAT BADUY LUAR TANPA SEKOLAH FORMAL MELALUI KELUARGA DAN TRADISI - Riyadi, Diva Dwi; Sapriya; Encep Supriatna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the informal education system of the Baduy community, which emphasizes cultural preservation and harmony with nature, rooted in family and traditional practices. Using qualitative methods and an ethnographic approach, this research reveals that education in the Baduy society centers on the transfer of customary values, practical skills, and community responsibility through direct practice. Findings highlight the central role of families in knowledge transfer and the community's resistance to formal education as a means of safeguarding cultural identity against modernization. The study underscores the importance of local wisdom-based approaches to inclusive education while offering recommendations for hybrid educational models that honor traditional values while maintaining modern relevance.